Research Processes and Indigenous Communities in Western Alaska: Workshop Report. - Raymond-Yakoubian, Brenden; Raymond-Yakoubian, Julie (Sandhill.Culture Craft and Kawerak, Inc., Social Sciences Program, 2017)
In August of 2016, Kawerak Incorporated and Sandhill.Culture.Craft partnered to hold a workshop in Nome, Alaska. The workshop was part of a larger project for this partnership which is looking at research processes and their relationships with Alaska indigenous communities. This project, an anthropology of northern research, treats this research itself as an object of study. The workshop brought together key indigenous voices from western and northern Alaska who have been highly involved in research. The goal of the workshop was to create a dialogue on the nature, concerns, and possible futures related to the relationships between research processes and indigenous communities. In turn, the workshop would (and did) provide valuable grounding to help guide future project activities, especially as they pertain to indigenous perspectives.